Association between abnormal plasma metabolism and brain atrophy in alcohol-dependent patients - Zhang, Zheyu; Zhang, Sifang; Huang, Jianhua; Cao, Xiaoyun; Hou, Chao; Luo, Zhihong; Wang, Xiaoyan; Liu, Xuejun; Li, Qiang; Zhang, Xi; Guo, Yujun; Xiao, Huiqiong; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective: In this study, we aimed to characterize the plasma metabolic profiles of brain atrophy and alcohol dependence patients (BA-ADPs) and to identify the underlying pathogenesis of brain atrophy related to alcohol dependence. Methods: We acquired the plasma samples of alcohol-dependent patients and performed non-targeted metabolomic profiling analysis to identify alterations of key metabolites in the plasma of BA-ADPs. Machine learning algorithms and bioinformatic analysis were also used to identify predictive biomarkers and investigate their possible roles in brain atrophy related to alcohol dependence. Results: A total of 26 plasma metabolites were significantly altered in the BA-ADPs group when compared with a group featuring alcohol-dependent patients without brain atrophy (NBA-ADPs). Nine of these differential metabolites were further identified as potential biomarkers for BA-ADPs. Receiver operating characteristic curves demonstrated that these potential biomarkers exhibited good sensitivity and specificity for distinguishing BA-ADPs from NBA-ADPs. Moreover, metabolic pathway analysis suggested that glycerophospholipid metabolism may be highly involved in the pathogenesis of alcohol‐induced brain atrophy. Conclusion: This plasma metabolomic study provides a valuable resource for enhancing our understanding of alcohol‐induced brain atrophy and offers potential targets for therapeutic intervention.